Professorial lecture : to clone or not to clone - and other ethical Issues In pharmacy and medicine / Abu Bakar bin Abdul Majeed. - Abdul Majeed, Abu Bakar (University Publication Centre (UPENA), UiTM, 2009)
In the last fifty years or so, advances in biotechnology, pharmacy and medicine have led to the introduction of novel and innovative products and procedures. Although these discoveries have provided benefits to patients, they have also created new ethical conundrums. Issues like human cloning, artificial reproductive technologies, genetic engineering, organ donation and transplant, stem cells research and euthanasia are becoming more pertinent and require a judicious approach to appease both practitioners and patients. The practice of pharmacy and medicine also requires a strong subscription to specific code of ethics. The discipline of bioethics, which encompasses medical ethics and pharmacoethics, has been introduced to provide an avenue for discussions on ethical practices in biotechnology, pharmacy and medicine. Bioethics can be defined as the study of the rightness and wrongness of acts performed within the discipline of life science, through the application of both ethical theory and case study method. The various moral questions pertaining to biotechnology, pharmacy and medicine in the contemporary world demand the adoption of applied ethics using ethical principles to solve real-life problems. However, simply adopting applied ethics based on secular approach may not be ideal. We must move effectively toward forging a meaningful dialogue between bioethics and religion, sometimes separated by a vast gap of misunderstanding, and mistrust and miscommunication. Religious principles and prescriptions must be the foundation for discussing ethical issues as the reason for religion's presence rests deep in the being of a species. It is to be argued that Muslims, for example, expect ethical solutions that are based on the principles of the shariah or Islamic law. By subscribing to this approach, in Islam ethical issues like therapeutic cloning, organ donation and transplant, and artificial insemination appear to have been mostly settled.